Adolescents' social representation about political Left- and Right-wing ideologies - Szabó, Ágnes; Fehér, Balázs; Miklós, Nóra; Szabó, Ádám (Видавництво Львівської політехніки, 2011)
In daily discourse people often talk about the ‘left’ and ‘right’ as a potential label of their political identity. Are these names just simple labels or do they have an underlying content? The social representations theory can be a conceptual framework to examine the core- and peripheral contents of ideologies. A plenty of research have investigated adults’ political views and thoughts, but only a few studies concentrated on teenagers’ opinion and concepts about ideologies. The aim of this paper (as a part of a bigger research) was to reveal adolescents’ social representations of the political Left and Right. Using the Five Words Association Method we attempted to explore the social representation of political Left and Right among adolescents. 228 high school students participated in the study. Data showed that the core structure of the representation is formed by current political actors, ideologies and symbolic contents, such as colors regardless to the wing. In addition, periphery mostly included actual-political contents, methods and tools of political activity. An affective evaluation also was characteristic for both sides, however, the direction varied. Left was associated more often with negative adjectives and deviant behavior. These findings refer to the importance of historical context.
Соціальне уявлення підлітків про ідеології політичного лівого та правого крил
Keywords: Left-wing; Right-wing; social representation; five words association method; adolescents